2015
DOI: 10.1590/0104-6632.20150322s00003048
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Production of 5-Hydroxymethylfurfural From Glucose in a Water: Acetone Biphasic System

Abstract: -5-Hydroxymethylfurfural (HMF) is considered to be an important building block for biorefineries and has a high potential for the production of chemicals and fuels. Production of HMF from glucose was studied using phosphoric acid as catalyst, in a water:acetone system with volume ratio of 1:2 and NaCl. An experimental design was applied to examine the influence of temperature, time and concentration of catalyst on the HMF yield. HMF yields of more than 50 % were obtained when using 200 °C, 8.4 min and 0.8% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In an initial evaluation, all of the factors seem to be important for the reaction since their maximum value was required for the highest HMF yield. In agreement with this observation, recent studies have demonstrated that the use of high temperature, high percentage of DMSO, long reaction time, and high amount of catalyst loading is advantageous for HMF synthesis. For instance, Pereira and co-workers demonstrated that high temperature is an important and key factor for the dehydration reaction of glucose in the HMF process . Probably, the influence of the temperature could be attributed to the considerable activation energy required for fructose dehydration into HMF using solid SO 3 H-acid functionalized catalyst (55–80 kJ mol –1 ), which is our case.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…In an initial evaluation, all of the factors seem to be important for the reaction since their maximum value was required for the highest HMF yield. In agreement with this observation, recent studies have demonstrated that the use of high temperature, high percentage of DMSO, long reaction time, and high amount of catalyst loading is advantageous for HMF synthesis. For instance, Pereira and co-workers demonstrated that high temperature is an important and key factor for the dehydration reaction of glucose in the HMF process . Probably, the influence of the temperature could be attributed to the considerable activation energy required for fructose dehydration into HMF using solid SO 3 H-acid functionalized catalyst (55–80 kJ mol –1 ), which is our case.…”
Section: Resultssupporting
confidence: 67%
“…5−14 For instance, Pereira and co-workers demonstrated that high temperature is an important and key factor for the dehydration reaction of glucose in the HMF process. 35 Probably, the influence of the temperature could be attributed to the considerable activation energy required for fructose dehydration into HMF using solid SO 3 H-acid functionalized catalyst (55−80 kJ mol −1 ), 38 which is our case. Note, however, that the temperature for the process cannot exceed 120 °C, since Amberlyst-15 is not stable above this maximum.…”
Section: ■ Results and Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Currently, HMF may be converted to numerous compounds [64], gas fuels or fuel additives, building blocks for the production of polymeric materials. To date, biorefinery based synthesis of HMF may be advantageous as it improves the use of biomass raw materials [65][66][67]. In addition, due to the significant weight loss of these LCMs after pre-treatment (Table 2), the need to effectively remove HMF and other inhibitors (Table 3), these lignocellulosic materials did not seem to be as attractive for use in the production of hydrogen through dark fermentation as we assumed at the beginning of the study.…”
Section: Inhibitory Compounds Formation During Alkaline Hydrolysismentioning
confidence: 93%